2017
DOI: 10.1016/j.jclinepi.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Series: Pragmatic trials and real world evidence: Paper 5. Usual care and real life comparators

Abstract: Pragmatic trials may deliver real-world evidence on the added value of new medications compared with usual care and inform decision making earlier in development. This fifth paper in a series on pragmatic trials in the Journal discusses usual care as a comparator and the allocation of treatment strategies. The allocation and implementation of treatment strategies should resemble clinical practice as closely as possible. Randomization at the level of the site, as opposed to at the individual level, may be prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 39 publications
2
36
0
1
Order By: Relevance
“…The concept of the so called seronegative APS (SNAPS) was introduced in 2003 to identify patients with highly suggestive manifestations of APS, but persistently negative for the classification laboratory criteria [144]. In the past 5 years, research has been focused on the identification of "new" aPL, not included in the serological criteria, in seronegative APS patients (3,20,22).…”
Section: Aps Loe5mentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of the so called seronegative APS (SNAPS) was introduced in 2003 to identify patients with highly suggestive manifestations of APS, but persistently negative for the classification laboratory criteria [144]. In the past 5 years, research has been focused on the identification of "new" aPL, not included in the serological criteria, in seronegative APS patients (3,20,22).…”
Section: Aps Loe5mentioning
confidence: 99%
“…Environmental and female-associated factors also play pathogenic roles in development of autoimmune diseases [1,2]. In last years, despite many progresses in managing these patients, it has been shown that clinical remission is reached in less than 50% of patients and a personalised and tailored therapeutic approach is still lacking resulting in a significant gap between guidelines and real-world practice [3,4]. In this context, the need for biomarkers facilitating early diagnosis and profiling those individuals at the highest risk for a poor outcome has become of crucial interest [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…But this abdication of responsibility does not wash with another group of pragmatists. In a critical rebuttal, the GetReal Consortium affirm strongly that the comparator choice dimension of a pragmatic trial should receive the same level of consideration as the other domains identified in PRECIS‐2. Their argument is that any gain in effectiveness claimed for the experimental treatment depends strongly on the nature of the comparator and that “usual care” provides a notoriously ambiguous “control,” in that (a) several usual care options may exist; (b) the alternatives may themselves vary from location to location (c) and over time; (d) less‐than optimal comparators may be selected in order to favour the latest intervention; (e) equipoise between treatment and comparator is easily disturbed, (f) the blinding of practitioners is difficult or abandoned; (g) cluster trials, whilst aiding concealment, are prone to selection and implementation bias; (h) strong patient preferences may shrink recruitment and subsequent participation; (i) treatments implemented and supervised by investigators may not correspond to local provision; and (j) changing from usual care to the new treatment may be affected by the restricted availability of the former.…”
Section: Methodsmentioning
confidence: 99%
“…Here we discuss PrCT definitions in the literature, propose a broad definition anchored on concepts used by others (including Hotopf 2002;MacPherson 2004;Zuidgeest et al 2017; the CONSORT statement updated for pragmatic studies (Zwarenstein et al 2008); and the PRECIS tool (Thorpe et al 2009)], and highlight several statistical challenges with potential solutions.…”
Section: Introductionmentioning
confidence: 99%